Antimicrobial resistant Escherichia coli isolates detected in raw milk of livestock in pastoral areas of northern Kenya - Ngaywa, C.; Aboge, G.O.; Obiero, G.; Omwenga, I.; Ngwili, N.; Wamwere-Njoroge, George J.; Wainaina, M.; Bett, Bernard K. (Elsevier, 2019)
Antimicrobial agents are used widely in veterinary and human medicine worldwide. However, their use has suffered a major setback globally due to the emergence of antimicrobial resistance (AMR) in a wide range of microorganisms. This study aimed to investigate the prevalence of AMR in household milk for human consumption in Isiolo County, Kenya. The study identified 42 Escherichia coli (E.coli) isolates from 304 milk samples that were collected in randomly selected households in northern Kenya. E. coli was isolated using Eosin Methylene Blue Agar and identified using biochemical tests. The isolates were confirmed using Polymerase Chain Reaction (PCR) and sequencing. The antimicrobial resistance profiles of the isolates to 11 antimicrobial agents were evaluated by disc diffusion method on Mueller Hinton Agar. Additionally, the isolates were evaluated for antimicrobial genetic determinants conferring the resistance phenotypes to beta-lactams and tetracycline. Overall, 95% of the isolates were resistant to at least one of the tested antimicrobials. Large proportions (81%) of the isolates were resistant to beta-lactams followed by tetracycline (55%) and streptomycin (29%). All the isolates were, however, susceptible to ciprofloxacin and nalidixic acid. Multidrug resistance (MDR) was observed in 14.28% of the isolates and beta-lactam resistant isolates were confirmed to be harbouring blaSHV, blaTEM and blaCTX-M genes. The demonstration of AMR determinants and especially Extended Spectrum Beta Lactamase (ESBL) carriers in milk reveals the risk posed to food safety, particularly to communities that consume raw milk. This study found that raw milk consumed in Isiolo County was contaminated with resistant strains of E. coli. There is, therefore, a need to determine the sources of this resistance and implement interventions to reduce the emergence and spread of AMR bacteria. We recommend implementation of measures that could reduce the presence of antimicrobial resistant E. coli strains in raw milk food chain.